Optimasi Manajemen Pelabuhan di Indonesia Timur melalui Teknologi Blockchain: Kajian Literatur - Ahmad Surajuddin Rauf; Djuanda Djuanda; Sangkala Sangkala; Muh. Djafar Mappa (Journal of Innovative and Creativity, 2025)
This study aims to analyze the potential application of blockchain technology to optimize port management in Eastern Indonesia. As an archipelagic nation, Indonesia relies heavily on ports, but the eastern region still faces limited infrastructure, complex bureaucracy, and high logistics costs, reaching 23–24% of GDP, far above the ASEAN average of around 14% (World Bank, 2024). The research method used was descriptive qualitative with a literature review approach (library research). Data were obtained from national and international journals, official government reports, and academic proceedings. The analysis was conducted using thematic analysis techniques, grouping the literature into themes of challenges, potential, obstacles, and recommendations. The results indicate that blockchain can improve transparency, efficiency, and accountability in the maritime supply chain. However, the main obstacles in Eastern Indonesia include limited internet access, low technological literacy, and the absence of supporting regulations. Practical implications of this research include the need for pilot projects in medium-sized ports, increasing digital literacy for operators and bureaucrats, developing internet infrastructure, and formulating regulations that support blockchain integration with the national logistics system.